THEORETICAL ASPECTS OF THE USE OF DIDACTIC METHODS IN STATE EDUCATIONAL STANDARDS IN TEACHING PRIMARY CLASS STUDENTS TO MODELING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the application of the modeling program to primary school students, its improvement, innovations in education, conformity of modeling to State educational standards, its use in the international assessment program PISA, as well as modeling thoughts and opinions about teaching through didactic methods are held.